Employing some Web 2.0 applications in developing the skills of producing digital stories for kindergarten teachers - Al-Sa'ida, Shoq Hasan (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the effectiveness of employing Web 2.0 applications in developing the skills of producing digital stories among kindergarten teachers. The semi-experimental approach was used to study the effect of the independent variable (Web 2.0 applications) on the dependent variable (digital story design skills). The tools of the study were a product evaluation card. A pre- and post-test was conducted to measure the effectiveness of using some Web 2.0 applications in developing digital story production skills. The test was applied to two groups: the first is an experimental one that uses the processing based on Web 2.0 applications, and the other is a control group that uses the traditional method. The study concluded that the average gain rate for Black was (1.26), which is greater than the minimum limit set by Black for effectiveness, and thus accepts the zero hypothesis of the effectiveness of using some Web 2.0 applications in developing digital story production skills. The study also recommended the use of Web 2.0 applications for its effectiveness in Developing digital story production skills among kindergarten teachers. It also recommended conducting training programs for teachers that help develop their awareness of using Web 2.0 applications in developing the level of educational production, as well as training programs for producing digital stories using Web 2.0 applications.